Assessment of Aerosol Mixtures of Different Viruses - Mayhew, Charles J. (1970)
Aerosol mixtures of the psittacosis agent, yellow fever virus, and variola virus were assayed by selective immunofluorescence in conjunction with fluorescent cell counting. The aerosol behavior of each agent could be readily delineated at test conditions of 80 F (26.67 C) and three relative humidities (30, 50, or 80%). Of the three agents, variola virus exhibited the lowest biological decay. The biological decay rates of the airborne agents were not significantly affected by humidity changes.